The influence of audit fee, audit tenure, audit rotation and client company size on audit quality - Rifki Ramdani (Institute of Accounting Research and Novation (IARN), 2022)
The objective of this research was to examine the influence of the fee audit, audit tenure, audit rotation, size of company and audit quality on financial sector enterprise. Fee audit, audit tenure, audit rotation and size of company as the independent variable. Audit Quality as the dependent variable. This study uses the basic theory is the agency theory. This study used secondary data obtained from the Indonesia Stock Exchange (IDX) during the period 2012-2014. The sampling process was done by using purposive sampling method and this study used 141 observations. The analyzing method to examine hypothesis was logistic regression analysis. The results shows that the size of company influence the audit quality. But for the fee audit, audit tenure, audit rotation no influence the audit quality.